Implementation of Professionalism and Spiritual Competencies of Christian Religious Education Teachers in Improving Learning Outcomes in the Form of Student Self-Transformation - Paendong, Samuel Geovany; Marbun, Purim (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2024)
Today, we often see behavioral practices that do not follow the values of the truth of God’s Word. Christian Religious Education’s role in fostering Christ’s character is indispensable in this condition. Christian religious education transforms the attitudes and behavior of individuals or groups to mature humans in all respects. Christian Religious Education must be an education that brings learners to experience changes in their lives. Teachers play an important role in the process of learning Christian Religious Education. In carrying out its role, a Christian Religious Education teacher is greatly influenced by professionalism and spiritual competence. Therefore, this study aims to describe the implementation of professionalism and spiritual competencies of Christian Religious Education teachers in improving student learning outcomes. The research method used qualitative data with descriptive and literature study techniques. The results showed that implementation of good and appropriate professionalism and spiritual competencies of teachers is very necessary in improving student learning outcomes in the form of self-transformation of learners, such as curriculum preparation, application of learning methods, learning evaluation, effective teacher communication with students and parents, mastery of subject matter by teachers, spiritual growth and exemplary of a teacher for his students.